PENGARUH DOSIS PUPUK ORGANIK BIO-SLURRY CAIR DAN WAKTU APLIKASI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L.) - Akari Edy; Resti Puspa Kartika Sari; Hidayat Pujisiswanto (Universitas Lampung, 2021)
Lampung is a center for maize and cattle production. This study aims to determine (1) the dosage of liquid bio-slurry fertilizer which is effective in increasing the growth and yield of maize, (2) the correct split application time of liquid bio-slurry, (3) the interaction between the dose of liquid bio-slurry fertilizer and time of split application on the growth and yield of maize. The research was conducted in Fajar Baru Village, Jati Agung District, South Lampung Regency. The study used a randomized block design (RBD) that arranged in factorial (4x2) with three replications. The first factor was the dosage of liquid bio-slurry organic fertilizer, namely 0 (control), 25, 50, and 75 l/ha. The second factor was the application time with 2 splits (2 and 4), and 3 splits (2, 4, and 6 weeks after planting, WAP). The results showed that: (1) The dose of liquid bio-slurry organic fertilizer 50 l/ha was effective in increasing plant growth and yield by producing stover dry weight of 57.17 g and dry shelled weight per harvest plot of 1.052 g/m2 or equivalent to 10.52 ton/ha; (2) application time of liquid bio-slurry organic fertilizer twice (2 and 4 WAP) or three times (2, 4, and 6 WAP) had no significant effect; (3) there was no interaction between the dosage of liquid bio-slurry organic fertilizer and application time on the growth and yield of maize. Keywords: bio-slurry, corn, dossage, liquid, split application